A Descriptive Study about Passion in Universitas Negeri Padang’s Alumni in the Workplace - Elrisfa Magistarina; Verlanda Yuca; Rahayu Hardianti Utami; Rahmi Dwi Febriani (Universitas Negeri Padang, 2021)
A supportive job is when someone enjoys their work; they feel that they can develop and achieve goals. In this context, supportive means a job that is related to their Passion. However, people nowadays seem to have dissatisfaction with their occupation that is not related to their Passion. It requires the students to get more information about their Passion and a job related to it before starting their careers. This study has 261 respondents that come from the alumni of UNP. The data collection was a questionnaire TYPI (Tari Yuca Passion Inventory) about Passion with 43-items and a descriptive statistic used to analyze the data. The result found that there was incongruence between their study and job that related to their Passion. Hence, the contribution of several stakeholders, such as the university, lecturers, academic advisors, and counseling service, is needed.